Gastrointestinal symptoms, inflammation and hypoalbuminemia in chronic kidney disease patients: a cross-sectional study. Issue 1 (December 2015) - Zhang, Xuehan; Bansal, Nisha; Go, Alan; Hsu, Chi-yuan
Abstract Background Few studies have focused on investigating hypoalbuminemia in patients during earlier stages of chronic kidney disease (CKD). In particular, little is known about the role of gastrointestinal (GI) symptoms. Our goal in this paper is to study how GI symptoms relate to serum albumin levels in CKD, especially in the context of and compared with inflammation. Methods We performed a cross-sectional study of 3599 patients with chronic kidney disease enrolled in the Chronic Renal Insufficiency Cohort (CRIC) study. All subjects were asked to complete the Modification of Diet in Renal Disease (MDRD) study patient symptom form. Our main predictor is GI symptom score. Serum level of C-reactive protein (CRP) was measured as well. Main outcome measures are serum albumin levels and prevalence of hypoalbuminemia. Results Of the participants assessed, mean serum albumin was 3.95 ± 0.46 g/dL; 12.7 % had hypoalbuminemia. Patients with lower estimated glomerular filtration rate (eGFR) were likely to have more GI symptoms (apparent at an eGFR <45 ml/min/1.73 m2 ). Patients with worse GI symptoms had lower dietary protein intake. GI symptoms, like inflammation, were risk factors for lower serum albumin levels. However, adding GI symptom score or CRP into the multivariable regression analysis, did not attenuate the association between lower eGFR and lower albumin or hypoalbuminemia. Conclusions Increased prevalence of GI symptoms become apparent among CKD patients at relatively high eGFR levels (45 ml/min/1.73 m2 ), long before ESRD. Patients with more severe GI symptoms scores are more likely to have hypoalbuminemia. But our data do not support GI symptoms/decreased protein intake or inflammation as being the main determinants of serum albumin level in CKD patients.